Competencias de la enfermera(o) especialista en el cuidado del paciente en urgencias y emergencia en instituciones hospitalarias - Aredo Tisnado, Helen Nolly (2019)
Qualitative study of descriptive approach whose object of study is to describe and analyze the skills of the specialist nurse in the care of the patient in emergency and urgency in the hospital institutions of Trujillo. It is based on the law of work, code of ethics and deontology of the Peruvian nurse, and the main theoretical approaches on competencies. The units of analysis were represented by 09 specialist nurses from the emergency services of the Regional Teaching Hospital, Belen Hospital of Trujillo and Víctor Lazarte Echegaray Hospital. A semi-structured interview was used to collect the information, then proceeded to perform the thematic analysis according to the units of meaning that emerged from the study units, resulting in competencies made up of 3 categories based on the person's understanding human, the management of hard and soft technologies, and essential values in care, each with its own subcategories that highlight its role in patient care in emergencies and urgencies in the hospital environment.